Pengaruh Struktur Modal, Kebijakan Dividen, Likuiditas, Solvabilitas Dan Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bei Tahun 2018-2021) - Jessi Charina Sembiring; Elisa Elisa; Divianny Violin Wijaya (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study to describe the effect of capital structure, dividend policy, liquidity, solvency and profitability on company value (case study of manufacturing companies in the food and beverage production sub-sector listed on the IDX in 2018-2021). The method implemented in the research is quantitative through purposive sampling, in the form of 11 manufacturing companies in the food and beverage production sub-sector listed on the Indonesia Stock Exchange in 2018-2021. Based on partial test, yhe results show that Capital Structure has no partial effect on firm value. Dividend Policy has no partial effect on firm value. Liquidity has no partial effect on firm value. Solvency has a partial effect on firm value. Profitability has a partial effect on firm value. Based on simultaneous test, Capital Structure, Dividend Policy, Liquidity, Solvency and Profitability have a simultaneous positive and significant impact on firm value with coefficient of determination of 26.9%. Keywords : Capital structure, dividend policy, liquidity, solvency, profitability, firm value